Avaliação de desempenho humano individual e em equipe em simulações interativas distribuídas de treinamento - Rocha, Rodrigo Vilela da (Universidade Federal de São Carlos, 2012)
The distributed interactive simulations can be used to train human actions and behaviors in dangerous situations, which way reduce the risks to life and/or patrimony. As part of the training in virtual environments, is important that learners are assessed not only after exercise virtual training, but also during this period that there may be occasional interventions by the coach in the learning process. However, the development of training simulations is complex and not always the human evaluation, post and share in real time, is offered to the learner as a learning resource and training support as coach. A computer systemis being developed in the WINDIS Laboratory at UFSCar s Computer Department, to support the modeling, construction, execution, management and control of complex training simulations, using emergency preparedness and response as application areas. This work is part of that system and aims to create an individual and/or group performance evaluation sub system in distributed interactive simulations in order to better train apprentices in emergency management processes. It had been used theories, methods and best practices for evaluating human performance to create this sub system. During the preparation of simulations and human performance evaluations, it had been used preparedness and response to emergencies standards and protocols for conducting drills accordingly to São Paulo State, as well as the support of professional experts (São Carlos Fire Department). The modeling, simulations and ontologies used in this project were developed by the students in an integrated manner at WINDIS laboratory. As an individual part of this paper, it has been developed three modules that enable, respectively, the training assessments configuration, the monitoring and evaluation at runtime (with proper measurement for the proposed scenario, the instructor interaction in the simulation and analysis of competences Individual and team), and the analysis and after-action orientation. Two scenarios were developed a concept proof, one for fire department truck s control panel and other to conduct fire-fighting with indirect attack.
Keywords: Sistemas distribuídos; Simulação; Pessoal - avaliação; Ambiente virtual colaborativo; Simulação de treinamento; Teorias de desempenho; Métodos qualitativos e quantitativos; Boas práticas de avaliação de desempenho; Medição de desempenho; Avaliação de desempenho; Simulation training; Collaborative virtual environment; Theories of performance; Qualitative and quantitative methods; Practice performance assessment; Performance measurement; Performance evaluation; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO